2008
DOI: 10.1021/jp711706z
|View full text |Cite
|
Sign up to set email alerts
|

Developing Ion Electroadsorption Stereoselectivity, by Pore Size Adjustment with Chemical Vapor Deposition onto Active Carbon Fiber Electrodes. Case of Ca2+/Na+ Separation in Water Capacitive Desalination

Abstract: By using carbon chemical vapor deposition (CVD) onto active porous carbon fibers, we were able to reduce the pore size of the active carbon to obtain selective carbon molecular sieves (CMS) of variable properties. The pore size of these carbons was characterized by the adsorption of molecules of different dimensions (molecular probe adsorption) from the gas phase. By manipulating the several experimental parameters of the CVD process, the pore size of the CMS could be finely tuned to fall between sizes of alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 22 publications
(41 reference statements)
1
53
0
Order By: Relevance
“…In the range of applied voltages from −0.5 to +0.8 V, no waves corresponding to redox reactions was observed. This behavior is typical for carbon materials . Note that the preliminary blowing of inert gas through the electrolyte can extend the electrochemical stability range to −0.8 … +1.0 V due to removal of adsorbed oxygen.…”
Section: Resultsmentioning
confidence: 70%
“…In the range of applied voltages from −0.5 to +0.8 V, no waves corresponding to redox reactions was observed. This behavior is typical for carbon materials . Note that the preliminary blowing of inert gas through the electrolyte can extend the electrochemical stability range to −0.8 … +1.0 V due to removal of adsorbed oxygen.…”
Section: Resultsmentioning
confidence: 70%
“…Planar solvated ions, like NO 3 − , are adsorbed in slit‐shaped pores, while spherical solvated ions, such as Cl − , are excluded. A similar study was carried out with Na + , Ca 2+ , and Mg 2+ which showed that electrosorption of hydrated monovalent sodium ions in micropores is preferred while the hydrated bivalent cations are excluded …”
Section: Electrical Double‐layer Capacitors (Edlcs)mentioning
confidence: 77%
“…New aspects have to be considered when decreasing the pore size of the carbon materials to the range of the ion sizes present in the system. Using carbons with an average pore size approaching the size of hydrated ions, Aurbach et al demonstrated it was possible to selectively electrosorb ions based on size . They defined this as ion sieving.…”
Section: Electrical Double‐layer Capacitors (Edlcs)mentioning
confidence: 99%
“…In commercial desalination technologies, such as reverse osmosis and multistage flash distillation, freshwater is produced at relatively high energy cost and often requires re-mineralization for human consumption. For brackish water or wastewater it can be advantageous to use a different type of technology, namely techniques where ions are removed from the feed water under the influence of electrical field effects, such as in electrodialysis [8,9], capacitive deionization [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], membrane capacitive deionization [29][30][31][32][33][34], desalination using microchannels [35], batteries [36], microbial desalination cells [37] and wires [38]. Such techniques have the potential to be energy-efficient as they focus on the removal of the (often relatively few) ions in the water to obtain freshwater in this way.…”
Section: Introductionmentioning
confidence: 99%